Differential Effects of Treatment Strategies in Individuals With Chronic Ocular Surface Pain With a Neuropathic Component - Patel, Sneh; Mittal, Rhiya; Felix, Elizabeth R.; Sarantopoulos, Konstantinos D.; Levitt, Roy C.; Galor, Anat (Frontiers in Pharmacology, 2021)
Background: Dysfunction at the ocular system via nociceptive or neuropathic mechanisms can lead to chronic ocular pain. While many studies have reported on responses to treatment for nociceptive pain, fewer have focused on neuropathic ocular pain. This retrospective study assessed clinical responses to pain treatment modalities in individuals with neuropathic component ocular surface pain. Methods: 101 individuals seen at the University of Miami Oculofacial Pain Clinic from January 2015 to August 2021 with ≥3 months of clinically diagnosed neuropathic pain were included. Patients were subcategorized (postsurgical, post-traumatic, migraine-like, and laterality) and self-reported treatment outcomes were assessed (no change, mild, moderate, or marked improvement). ANOVA (analysis of variance) was used to examine relationships between follow up time and number of treatments attempted with pain improvement, and multivariable logistic regression was used to assess which modalities led to pain improvement. Results: The mean age was 55 years, and most patients were female (64.4%) and non-Hispanic (68.3%). Migraine-like pain (40.6%) was most common, followed by postsurgical (26.7%), post-traumatic (16.8%) and unilateral pain (15.8%). The most common oral therapies were α2δ ligands (48.5%), the m common topical therapies were autologous serum tears (20.8%) and topical corticosteroids (19.8%), and the most common adjuvant was periocular nerve block (24.8%). Oral therapies reduced pain in post-traumatic (81.2%), migraine-like (73%), and unilateral (72.7%) patients, but only in a minority of postsurgical (38.5%) patients. Similarly, topicals improved pain in post-traumatic (66.7%), migraine-like (78.6%), and unilateral (70%) compared to postsurgical (43.7%) patients. Non-oral/topical adjuvants reduced pain in postsurgical (54.5%), post-traumatic (71.4%), and migraine-like patients (73.3%) only. Multivariable analyses indicated migraine-like pain improved with concomitant oral α2δ ligands and adjuvant therapies, while postsurgical pain improved with topical anti-inflammatories. Those with no improvement in pain had a shorter mean follow-up (266.25±262.56 days) than those with mild (396.65±283.44), moderate (652±413.92), or marked improvement (837.93±709.35) (p<0.005). Identical patterns were noted for number of attempted medications. Conclusion: Patients with migraine-like pain frequently experienced pain improvement, while postsurgical patients had the lowest response rates. Patients with a longer follow-up and who tried more therapies experienced more significant relief, suggesting multiple trials were necessary for pain reduction.